Negative electrode composite material, preparation method thereof and lithium ion battery
By using the negative electrode composite structure of core, amorphous carbon cladding and graphene cladding in lithium-ion batteries, the problem of volume expansion and poor structural stability of the negative electrode material during circulation is solved, and the circulation performance and energy are improved density.
Patent Information
- Application Number
- CN202411440284.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
AI Technical Summary
The existing lithium-ion battery negative electrode materials are prone to volume expansion during circulation, poor structural stability, resulting in poor circulation performance and low energy density.
Using an inside-out negative electrode composite structure, including a core, amorphous carbon cladding and graphene cladding, the core consists of silver and copper elements. Silver elements are used as lithium-philic sites to induce uniform deposition of lithium, and copper elements Helps to form a stable amorphous carbon cladding, graphene cladding builds a three-dimensional limit domain framework structure, inhibiting expansion and active site failure.
The stability and cycling performance of the negative electrode sheet are improved, the energy density of the lithium-ion battery is enhanced, and the combination of the dual-domain skeleton structure and conductive materials effectively suppresses volume expansion and electronic transmission path extension.
Smart Images

Figure CN119275273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode composite material, a preparation method thereof and a lithium ion battery. Background Art
[0002] With the popularity of consumer electronic products such as laptops, mobile phones, handheld game consoles, tablets, mobile power supplies and drones, people have higher and higher requirements for the electrochemical devices (such as batteries) therein. For example, people not only require batteries to be lightweight, but also require batteries to have short charging times and long working lives. Among the many batteries, lithium-ion batteries have attracted much attention in the field of research and development due to their highest energy density. At present, how to improve the structural stability of the negative electrode has become the research and development focus in the field of lithium-ion batteries.
[0003] Lithium metal has an extremely low chemical potential (-3.04V), an extremely high theoretical specific capacity (3860mAh / g) and a very high reactivity, which can greatly improve the energy density and is the most ideal negative electrode material. Although the energy density can be greatly improved by using lithium metal as the negative electrode material, the cycle life of the battery will also be sharply shortened. The main factors affecting the structural stability of lithium metal negative electrodes are: (1) The lithium deposition on the one-dimensional lithium metal plane has a "tip effect". The uneven lithium deposition will induce the formation of lithium dendrites, causing dead lithium, leading to puncturing the diaphragm short circuit and even thermal runaway of the battery; (2) As the negative electrode active material, lithium metal will expand the volume of the negative electrode during repeated deposition and stripping, and the accumulation of dead lithium and the failure of active sites will cause the cycle performance to deteriorate.
[0004] The existing document (publication number CN115172670A) discloses a silver-carbon composite metal lithium negative electrode and a preparation method thereof. The silver-carbon composite metal lithium negative electrode is a negative electrode material attached to the surface of a copper foil, and the negative electrode material is composed of a silver-carbon composite negative electrode material and deposited lithium; the preparation method of the negative electrode material comprises: 1) immersing a carbon-based material resin in a silver nitrate solution, and obtaining ion exchange resin microspheres after Ag substitution after sufficient reaction; 2) carbonization treatment; 3) making a slurry of the silver-carbon composite negative electrode material and applying it to the copper foil to obtain a copper foil with a silver-carbon composite negative electrode material coating attached to the surface; 4) slicing the copper foil with the coating, and assembling and discharging a Cu / Li half-cell; 5) taking out the discharged half-cell copper foil to obtain a silver-carbon composite metal lithium negative electrode after lithium deposition. Although this document can solve the technical problems of lithium dendrite formation and uneven lithium deposition in existing metal lithium negative electrodes, it does not provide effective mitigation measures on the surface layer for the volume expansion problem caused by repeated alloying and dealloying of lithium and silver due to the separation of dispersed silver from lithium during the cycle. Moreover, silver is prone to separation due to volume expansion during the cycle, and broken silver will migrate with lithium. The migration of fragmented silver will change its initial uniform site, and the silver site lacking confined space will also lose the function of uniform lithium deposition, which will reduce the cycle life of the battery and easily cause battery capacity decay and increase the risk of failure.
[0005] In summary, it is of great significance to study and develop a negative electrode composite material, a preparation method thereof, and a lithium-ion battery that can induce uniform lithium deposition, alleviate volume expansion, and have a stable negative electrode structure and excellent cycle performance and rate performance. Summary of the invention
[0006] The main purpose of the present invention is to provide a negative electrode composite material, a preparation method thereof and a lithium ion battery, so as to solve the problem in the prior art that the negative electrode material is prone to volume expansion during the cycle, has poor structural stability, and leads to poor cycle performance and low energy density.
[0007] In order to achieve the above objectives, the first aspect of the present invention provides a negative electrode composite material, which comprises, from the inside to the outside, a core, an amorphous carbon coating layer and a graphene coating layer, wherein the core comprises silver and copper elements.
[0008] Furthermore, the core is a silver-copper alloy having the general formula Ag x Cu 100-x , wherein x is any value between 15 and 90; preferably, x is any value between 40 and 90.
[0009] Furthermore, the average particle size of the inner core is 500 to 3000 nm.
[0010] Furthermore, the thickness of the amorphous carbon coating layer is 5 to 20 nm.
[0011] Furthermore, the thickness of the graphene coating layer is 100 to 500 nm.
[0012] Further, the graphene coating layer comprises a graphene porous material; preferably, the graphene coating layer has a porosity of 20-50% and a specific surface area of 50-250 cm 2 / g.
[0013] The second aspect of the present application also provides a method for preparing the above-mentioned negative electrode composite material provided by the present application, and the preparation method includes: step S1, mixing a precursor solution containing silver and copper elements with a dispersant and causing a first reduction reaction under the action of a first reducing agent to obtain a core; step S2, under inert atmosphere conditions, depositing an amorphous carbon coating layer on the surface of the core to obtain a core with an amorphous carbon coating layer on the surface; wherein a carbon source is introduced during the deposition process; step S3, mixing the core with an amorphous carbon coating layer on the surface with a graphene oxide dispersion and causing a second reduction reaction under the action of a second reducing agent, and obtaining the negative electrode composite material after a first drying.
[0014] Furthermore, the preparation method of the precursor solution includes: mixing silver salt, copper salt and water to obtain a precursor solution; preferably, the molar ratio of the silver element in the silver salt to the copper element in the copper salt is x:(100-x), wherein x is any value between 15 and 90, and more preferably x is any value between 40 and 90.
[0015] Furthermore, the molar ratio of the silver salt, the copper salt and the dispersant is (1-8):1:1.
[0016] Furthermore, the molar ratio of the silver salt, the copper salt and the first reducing agent is (1-5):1:2.
[0017] Further, the silver salt is selected from one or more of the group consisting of silver nitrate, silver sulfate and silver acetate.
[0018] Further, the copper salt is selected from one or more of the group consisting of copper nitrate, copper sulfate, copper acetate, copper chloride and basic copper sulfate.
[0019] Furthermore, the dispersant is selected from one or more of the group consisting of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, carboxymethyl cellulose, polyacrylamide, guar gum and fatty acid polyethylene glycol ester; preferably, the weight average molecular weight of polyvinyl pyrrolidone is 4000-130000.
[0020] Furthermore, the temperature of the first reduction reaction is 170-200° C., and the time is 20-40 minutes.
[0021] Furthermore, the deposition is performed by chemical vapor deposition, and preferably the deposition temperature is 900-1000° C. and the deposition time is 60-360 min.
[0022] Furthermore, the ratio of the weight of the inner core to the volume of the carbon source is (20-100) mg: (2100-12600) mL.
[0023] Furthermore, the carbon source is selected from C 1 ~C 4 One or more hydrocarbon compounds; more preferably selected from C 1 ~C 4 One or more of the alkanes.
[0024] Furthermore, the inert atmosphere is selected from argon, or a mixture of hydrogen and nitrogen, or a mixture of hydrogen, nitrogen and argon.
[0025] Furthermore, step S3 comprises: mixing the core with the amorphous carbon coating layer on the surface, the graphene oxide dispersion, the salt and the solvent and performing a second reduction reaction under the action of a second reducing agent, and obtaining the negative electrode composite material after washing and first drying in sequence.
[0026] Furthermore, the temperature of the second reduction reaction is 60-90° C., and the time is 6-24 hours.
[0027] Further, the first reducing agent and the second reducing agent are each independently selected from one or more of the group consisting of ethylene glycol, hydrazine hydrate, vinylene carbonate, thiourea, hydroiodic acid, urea, ascorbic acid, n-butanol, sodium bisulfite and sodium citrate.
[0028] Further, the salt is selected from KMnO 4 、Na 2 S 2 O 3 、FeCl 3 and Fe 2 (SO 4 ) 3 One or more of the group consisting of; preferably, the solvent is water.
[0029] Furthermore, a cleaning agent is used for washing, and preferably the cleaning agent is selected from ethanol and / or water.
[0030] Furthermore, the first drying temperature is 60-80° C. and the time is 6-24 hours.
[0031] Furthermore, the second reduction reaction is carried out under disturbance conditions, and the disturbance is selected from at least one of stirring, shaking and ultrasound; preferably, the stirring speed is 100-200 rpm, the shaking frequency is 10-30 Hz, and the ultrasound frequency is 30-50 Hz.
[0032] Furthermore, the preparation method of the graphene oxide dispersion includes: mixing graphene oxide with water to obtain a graphene oxide dispersion; preferably, the mass concentration of graphene oxide is 6 to 10 mg / mL; and preferably, ultrasonic treatment is performed during the mixing of graphene oxide and water.
[0033] Furthermore, the weight ratio of graphene oxide, salt and the second reducing agent is 1:(0.256-0.9):(1-9).
[0034] Furthermore, step S1 includes: mixing the precursor solution with the dispersant and causing a first reduction reaction under the action of the first reducing agent, and obtaining the inner core after centrifugal treatment and second drying in sequence; preferably, the centrifugal treatment speed is 8000-15000 rpm, and the time is 10-30 min; preferably, the second drying temperature is 60-80°C, and the time is 6-12 h.
[0035] The third aspect of the present application also provides a lithium-ion battery, including a positive electrode plate, a negative electrode plate, an electrolyte and a separator arranged between the positive electrode and the negative electrode; wherein the negative electrode plate includes a negative electrode collector, a negative electrode active material layer and a metallic lithium layer stacked in sequence, and the metallic lithium layer is arranged between the negative electrode active material layer and the separator, wherein the negative electrode active material layer includes the above-mentioned negative electrode composite material provided in the present application.
[0036] Applying the technical solution of the present invention, the traditional negative electrode material includes a core containing only silver elements and a carbon coating layer arranged on the surface of the core, which can only improve the problem of lithium dendrite growth, but cannot solve the problem of volume expansion. However, the negative electrode composite material provided by the present application includes a core, an amorphous carbon coating layer and a graphene coating layer from the inside to the outside, wherein the core includes silver elements and copper elements, and the silver element is used as a lithium-philic site, which can induce the uniform deposition and nucleation of lithium in the lithium-ion battery during the cycle process. Silver has a good ability to alloy and de-alloy with lithium, and ensures the long-term effectiveness of the lithium-philic sites in the negative electrode active material layer in the negative electrode sheet during repeated lithium deposition and stripping, thereby inhibiting the growth of lithium dendrites and alleviating the "tip effect". The introduction of copper elements can facilitate the subsequent deposition to form an amorphous carbon coating layer with a more stable structure. The amorphous carbon coating layer and the graphene coating layer constitute a three-dimensional confined skeleton structure, thereby providing more space to accommodate lithium and inhibiting the expansion of the negative electrode composite material and the negative electrode sheet. Under the dual effects of the amorphous carbon coating and the graphene coating, the lithiophilic silver sites in the inner core can be restricted and fixed in a uniformly distributed position. At the same time, the dual confined skeleton structure formed by the two not only provides space for the volume expansion of the negative electrode composite material, but also confines the changes brought about by the volume expansion within the structure. The change refers to the detachment of the silver sites due to volume expansion and migration with the lithium, resulting in the failure of the active sites, thereby improving the stability of the negative electrode sheet, and further improving the cycle performance of the lithium-ion battery.
[0037] The amorphous carbon coating and the graphene coating themselves have excellent electrical conductivity. The amorphous carbon coating is slip-connected to the graphene coating, which facilitates the conduction of electrons from the graphene coating to the lithiophilic silver sites, constructing an internally and externally interconnected electronic network, effectively shortening the electron transmission path, and improving the electron transmission efficiency, thereby increasing the energy density of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0039] Figure 1 The scanning electron microscope image (SEM image) of the core prepared in Example 1 of the present application is shown;
[0040] Figure 2 The scanning electron microscope image (SEM image) of the negative electrode composite material prepared in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0041] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0042] As described in the background technology, the existing lithium metal negative electrode materials have the problems of easy volume expansion, poor structural stability, poor cycle performance and low energy density during the cycle. In order to solve the above technical problems, the first aspect of the present application provides a negative electrode composite material, which includes a core, an amorphous carbon coating layer and a graphene coating layer from the inside to the outside, wherein the core includes silver and copper elements.
[0043] Traditional negative electrode materials include a core containing only silver elements and a carbon coating layer arranged on the surface of the core, which can only improve the problem of lithium dendrite growth, but cannot solve the problem of volume expansion. However, the negative electrode composite material provided by the present application includes a core, an amorphous carbon coating layer and a graphene coating layer from the inside to the outside, wherein the core includes silver elements and copper elements, and the silver element is used as a lithium-philic site, which can induce the uniform deposition and nucleation of lithium in the lithium-ion battery during the cycle process. Silver has a good ability to alloy and de-alloy with lithium, and ensures the long-term effectiveness of the lithium-philic sites in the negative electrode active material layer in the negative electrode sheet during repeated lithium deposition and stripping, thereby inhibiting the growth of lithium dendrites and alleviating the "tip effect". The introduction of copper elements can facilitate the subsequent deposition to form an amorphous carbon coating layer with a more stable structure. The amorphous carbon coating layer and the graphene coating layer constitute a three-dimensional confined skeleton structure, thereby providing more space to accommodate lithium and inhibiting the expansion of the negative electrode composite material and the negative electrode sheet. Under the dual effects of the amorphous carbon coating and the graphene coating, the lithiophilic silver sites in the inner core can be restricted and fixed in a uniformly distributed position. At the same time, the dual confined skeleton structure formed by the two not only provides space for the volume expansion of the negative electrode composite material, but also confines the changes brought about by the volume expansion within the structure. The change refers to the detachment of the silver sites due to volume expansion and migration with the lithium, resulting in the failure of the active sites, thereby improving the stability of the negative electrode sheet, and further improving the cycle performance of the lithium-ion battery.
[0044] The amorphous carbon coating and the graphene coating themselves have excellent electrical conductivity. The amorphous carbon coating is slip-connected to the graphene coating, which facilitates the conduction of electrons from the graphene coating to the lithiophilic silver sites, constructing an internally and externally interconnected electronic network, effectively shortening the electron transmission path, and improving the electron transmission efficiency, thereby increasing the energy density of lithium-ion batteries.
[0045] In a preferred embodiment, the core is a silver-copper alloy having the general formula Ag x Cu 100-x, wherein x is any value between 15 and 90. The above x and (100-x) are molar contents, and the molar ratio of silver element to copper element in the silver-copper alloy includes but is not limited to the above range. Limiting it within the above range is conducive to making the average particle size of the core within a more suitable range, and is conducive to providing enough lithium-philic silver sites for the negative electrode composite material, and is conducive to making the lithium deposition of the lithium ion battery more uniform during the cycle process, thereby being conducive to inhibiting the growth of lithium dendrites and alleviating the "tip effect", thereby being conducive to improving the structural stability of the negative electrode composite material and improving the cycle performance of the prepared lithium ion battery.
[0046] In order to further make the average particle size of the inner core within a more suitable range, further make the lithium deposition more uniform, further inhibit the growth of lithium dendrites, further alleviate the "tip effect", and thus further improve the structural stability of the negative electrode composite material, preferably, x takes any value between 40 and 90.
[0047] In a preferred embodiment, the average particle size of the core is 500 to 3000 nm. The average particle size of the core includes but is not limited to the above range. Limiting it within the above range is conducive to improving the density of the core, making lithium deposition more uniform during the cycle of the lithium-ion battery, and making the lithium-philic sites in the negative electrode active material layer in the negative electrode sheet effective for a long time during repeated lithium deposition and stripping, thereby helping to inhibit the growth of lithium dendrites, thereby helping to improve the structural stability of the negative electrode composite material and improve the cycle performance of the lithium-ion battery.
[0048] In a preferred embodiment, the thickness of the amorphous carbon coating layer is 5 to 20 nm. The thickness of the amorphous carbon coating layer includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the specific surface area, conductivity and structural stability of the negative electrode composite material. At the same time, the amorphous carbon coating layer is beneficial to restricting and fixing the lithium-philic silver sites in the core to a more evenly distributed position, and is also beneficial to providing more space for the volume expansion of the negative electrode composite material, and is beneficial to confining the changes caused by the volume expansion inside the structure. The change refers to the silver sites detaching and migrating with lithium due to volume expansion, resulting in the failure of the active sites, which is beneficial to improving the structural stability of the negative electrode composite material, and then to improving the cycle performance and energy density of the lithium-ion battery.
[0049] In a preferred embodiment, the thickness of the graphene coating layer is 100 to 500 nm. The thickness of the graphene coating layer includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the conductivity of the negative electrode composite material, thereby improving the energy density of the lithium ion battery, and is also beneficial to the interaction between the graphene coating layer and the amorphous carbon coating layer connected thereto by slip to form a three-dimensional confined skeleton structure, which is beneficial to limiting and fixing the lithium-philic silver sites in the inner core to a more evenly distributed position, and is beneficial to inhibiting the growth of lithium dendrites; on the other hand, it is also beneficial to provide more space for the volume expansion of the negative electrode composite material, and is beneficial to confine the changes caused by the volume expansion within the structure, thereby improving the structural stability of the negative electrode composite material, and further improving the cycle performance of the lithium ion battery.
[0050] In a preferred embodiment, the graphene coating layer includes a graphene porous material. The graphene porous material has a pore structure, which is conducive to providing more space for accommodating lithium, thereby facilitating the suppression of the expansion of the negative electrode composite material and the negative electrode sheet, and is also conducive to improving the transmission efficiency of electrons, thereby facilitating the improvement of the energy density of the lithium-ion battery.
[0051] In order to further provide more space for accommodating lithium, thereby further suppressing the expansion of the negative electrode composite material and the negative electrode sheet, and at the same time further improving the transmission efficiency of electrons, thereby further improving the energy density of lithium-ion batteries, preferably, the porosity of the graphene coating layer is 20-50%, and the specific surface area is 50-250cm 2 / g.
[0052] The second aspect of the present application also provides a method for preparing the above-mentioned negative electrode composite material, which comprises: step S1, mixing a precursor solution containing silver and copper elements with a dispersant and causing a first reduction reaction under the action of a first reducing agent to obtain a core; step S2, under inert atmosphere conditions, depositing an amorphous carbon coating layer on the surface of the core to obtain a core with an amorphous carbon coating layer on the surface; wherein a carbon source is introduced during the deposition process; step S3, mixing the core with an amorphous carbon coating layer on the surface with a graphene oxide dispersion and causing a second reduction reaction under the action of a second reducing agent to obtain a negative electrode composite material after a first drying.
[0053] In step S1, since the standard potential of Ag is higher than that of Cu, in the first reduction reaction, Ag + The first reduction reaction to generate Ag occurs faster, which makes the unreduced Cu in the precursor solution 2+ Replacement reaction with Ag to form Ag x Cu 100-xalloy; silver element as a lithium-philic site can induce lithium uniform deposition nucleation in the lithium-ion battery during the cycle process, and silver element has good ability to alloy and de-alloy with lithium, and ensures the long-term effectiveness of the lithium-philic sites in the negative electrode active material layer in the negative electrode plate during repeated lithium deposition and stripping, thereby inhibiting the growth of lithium dendrites, alleviating the "tip effect", and improving the structural stability of the negative electrode composite material; during the deposition process, the copper element in the core can play its catalytic role, so as to facilitate the deposition of an amorphous carbon coating layer on the surface of the core in step S2, and obtain a core with an amorphous carbon coating layer on the surface; the dispersant and the core can form a tight adsorption layer, and the introduction of the dispersant can inhibit the agglomeration between the core particles, thereby improving the distribution uniformity of the silver-copper alloy, and the dispersant can also play the role of a surfactant, thereby improving the reaction efficiency of the first reduction reaction.
[0054] Under inert atmosphere conditions, an amorphous carbon coating layer is deposited on the surface of the inner core. The inert atmosphere conditions can inhibit the oxidation of the inner core. The amorphous carbon coating layer can provide space for the volume expansion of the negative electrode composite material, improve the structural stability of the negative electrode composite material, and thus improve the cycle performance and of the lithium-ion battery. By performing the above step S3, a negative electrode composite material can be obtained, which includes a core, an amorphous carbon coating layer and a graphene coating layer from the inside to the outside; wherein the carbon coating layer and the graphene coating layer constitute a three-dimensional confined skeleton structure, thereby being able to provide more space for accommodating lithium and inhibiting the expansion of the negative electrode composite material, the negative electrode and the sheet; under the dual action of the amorphous carbon coating layer and the graphene coating layer, the lithium-philic silver sites in the core can be confined and fixed in a uniformly distributed position, and at the same time, the dual confined skeleton structure formed by the two provides space for the volume expansion of the negative electrode composite material and at the same time confines the changes brought about by the volume expansion inside the structure, the change refers to the silver sites being detached and migrating with the lithium due to the volume expansion, resulting in the failure of the active sites, thereby improving the stability of the negative electrode sheet, and further improving the cycle performance of the lithium-ion battery. The amorphous carbon coating and the graphene coating themselves have excellent electrical conductivity. The amorphous carbon coating is slip-connected to the graphene coating, which facilitates the conduction of electrons from the graphene coating to the lithiophilic silver sites, constructing an internally and externally interconnected electronic network, effectively shortening the electron transmission path, and improving the electron transmission efficiency, thereby increasing the energy density of lithium-ion batteries.
[0055] In a preferred embodiment, the method for preparing the precursor solution includes: mixing a silver salt, a copper salt and water to obtain a precursor solution. Compared with other methods, the method for preparing the precursor solution is advantageous in that the silver salt and the copper salt are pre-mixed uniformly, thereby facilitating improving the reaction efficiency of the first reduction reaction.
[0056] In order to further improve the reaction efficiency of the first reduction reaction and thereby provide silver elements for the inner core, preferably, the silver salt includes but is not limited to one or more of the group consisting of silver nitrate, silver sulfate and silver acetate.
[0057] In order to further improve the reaction efficiency of the first reduction reaction and thereby provide copper elements for the inner core, preferably, the copper salt includes but is not limited to one or more of the group consisting of copper nitrate, copper sulfate, copper acetate, copper chloride and basic copper sulfate.
[0058] In a preferred embodiment, the molar ratio of the silver element in the silver salt to the copper element in the copper salt is x:(100-x), wherein x is any value between 15 and 90. The molar ratio of the silver element in the silver salt to the copper element in the copper salt includes but is not limited to the above range. Limiting it within the above range is conducive to making the average particle size of the core within a more suitable range, providing enough lithium-philic silver sites for the negative electrode composite material, and making the lithium deposition of the lithium ion battery more uniform during the cycle, thereby facilitating the inhibition of the growth of lithium dendrites and alleviating the "tip effect", thereby facilitating the improvement of the structural stability of the negative electrode composite material and the improvement of the cycle performance of the prepared lithium ion battery; at the same time, during the deposition process, it is conducive to better exerting the catalytic effect of the copper element in the core, thereby improving the deposition effect of the amorphous carbon coating layer and obtaining a core with an amorphous carbon coating layer coated on the surface.
[0059] In order to further make the average particle size of the inner core within a more suitable range, further induce uniform nucleation of lithium deposition, further inhibit the growth of lithium dendrites, thereby further improving the structural stability of the negative electrode composite material, and at the same time to further improve the deposition effect of the amorphous carbon coating layer, preferably, x takes any value between 40 and 90.
[0060] In a preferred embodiment, the molar ratio of the silver salt, the copper salt and the dispersant is (1-8): 1: 1. Compared with other ranges, limiting the molar ratio of the silver salt, the copper salt and the dispersant to the above range is conducive to improving the reaction efficiency of the first reduction reaction, and is conducive to inhibiting the agglomeration of the core particles obtained by the first reduction reaction, thereby helping to improve the distribution uniformity of the silver-copper alloy.
[0061] In a preferred embodiment, the dispersant includes, but is not limited to, one or more of the group consisting of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, carboxymethyl cellulose, polyacrylamide, gum and fatty acid polyethylene glycol esters. Compared with other types, the above-mentioned dispersant can form a tighter adsorption layer with the core, and the hydrocarbon chains in the dispersant macromolecules can extend outward to form a space barrier, which is beneficial to inhibit the agglomeration between the core particles, and further to improve the distribution uniformity of the silver-copper alloy, and also to play the role of the surfactant, so as to improve the reaction efficiency of the first reduction reaction.
[0062] In order to further inhibit the agglomeration of the core particles, further improve the distribution uniformity of the silver-copper alloy, and also to further exert its surfactant effect, thereby further improving the reaction efficiency of the first reduction reaction, preferably, the weight average molecular weight of polyvinyl pyrrolidone is 4000-130000.
[0063] An excess of the first reducing agent will cause a violent reaction, which will cause the kernel particle size to be too large, and the kernel growth rate is greater than the nucleation rate, which will lead to poor density of the kernel. In a preferred embodiment, the molar ratio of the silver salt, the copper salt and the first reducing agent is (1-5): 1: 2. The molar ratio of the silver salt, the copper salt and the first reducing agent includes but is not limited to the above range. Limiting it to the above range is conducive to improving the reaction efficiency of the first reduction reaction, improving the yield of the kernel, making the particle size of the obtained kernel within a more suitable range, and improving the density of the kernel.
[0064] In order to further improve the reaction efficiency of the first reduction reaction and further improve the yield of the inner core, preferably, the temperature of the first reduction reaction is 170-200° C. and the time is 20-40 min.
[0065] Chemical vapor deposition is a method of decomposing the vapor of a carbon-containing gas or liquid reactant under high temperature conditions into a carbon source, which is deposited on the surface of the material to form a coated carbon layer. In a preferred embodiment, chemical vapor deposition is used for deposition. Compared with other deposition methods, chemical vapor deposition is advantageous for obtaining an amorphous carbon coating layer with uniform coating thickness.
[0066] In a preferred embodiment, the deposition temperature is 900-1000°C and the deposition time is 60-360 minutes. The deposition temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the deposition effect, thereby improving the density and uniformity of the amorphous carbon coating layer, and also helping to improve the bonding force between the amorphous carbon coating layer and the core.
[0067] In a preferred embodiment, the ratio of the weight of the kernel to the volume of the carbon source is (20-100) mg: (2100-12600) mL. The ratio of the weight of the kernel to the volume of the carbon source includes but is not limited to the above range, and limiting it within the above range is conducive to obtaining an amorphous carbon coating layer with a more suitable thickness, thereby facilitating the improvement of the specific surface area, conductivity and structural stability of the negative electrode composite material, providing more space for the volume expansion of the negative electrode composite material, and improving the structural stability of the negative electrode composite material, thereby facilitating the improvement of the cycle performance and energy density of the lithium ion battery.
[0068] In order to further obtain a core with an amorphous carbon coating layer on the surface, further provide more space for the volume expansion of the negative electrode composite material, thereby further improving the structural stability of the negative electrode composite material, preferably, the carbon source includes but is not limited to C 1 ~C 4 More preferably, including but not limited to C 1 ~C 4 One or more of the alkanes.
[0069] In order to inhibit the silver-copper alloy in the core from being oxidized during the deposition process, in a preferred embodiment, the inert atmosphere includes but is not limited to argon, or a mixture of hydrogen and nitrogen, or a mixture of hydrogen, nitrogen and argon.
[0070] In a preferred embodiment, step S3 comprises: mixing the core with an amorphous carbon coating layer on the surface, the graphene oxide dispersion, the salt and the solvent and subjecting the core to a second reduction reaction under the action of a second reducing agent, and then washing and first drying the core to obtain a negative electrode composite material.
[0071] The surface of graphene oxide contains more oxygen-containing functional groups, which provide more binding sites for salt ions, so that graphene oxide and salt ions are tightly combined. Salt is introduced in the second reduction reaction, and is reduced to insoluble nanoparticles in the second reduction reaction process. The nanoparticles are attached to the graphene oxide sheets, which promotes the overlap of the graphene sheets and is conducive to improving the close combination of the graphene sheets and the amorphous carbon coating layer. After washing and removing the insoluble nanoparticles, pores can be formed at the positions of the original insoluble nanoparticles on the graphene sheets, which is conducive to improving the transmission efficiency of electrons, and then to improving the energy density of lithium-ion batteries.
[0072] In a preferred embodiment, the temperature of the second reduction reaction is 60 to 90° C., and the time is 6 to 24 hours. The temperature and time of the second reduction reaction include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the efficiency of the second reduction reaction and improving the coating effect of the graphene coating layer, thereby helping to better play the role of inhibiting the volume expansion of the negative electrode composite material.
[0073] In order to further improve the reaction efficiency of the first reduction reaction and the second reduction reaction, further improve the yield of the inner core, and further improve the coating effect of the graphene coating layer, preferably, the first reducing agent and the second reducing agent each independently include but are not limited to one or more of the group consisting of ethylene glycol, hydrazine hydrate, vinylene carbonate, thiourea, hydroiodic acid, urea, ascorbic acid, n-butanol, sodium bisulfite and sodium citrate.
[0074] In a preferred embodiment, the salt includes but is not limited to KMnO 4 、Na 2 S 2 O 3 、FeCl 3 and Fe 2 (SO 4 ) 3 Compared with other types, the above-mentioned salts are all high-valent soluble salts, which are convenient for them to be reduced to form insoluble nanoparticles in the second reduction reaction, which is beneficial to promote the overlapping and tight bonding of graphene sheets in the process of assembling to form graphene coating layers, and is beneficial to improve the energy density of negative electrode composite materials.
[0075] In order to improve the compatibility of the salt with the solvent, preferably, the solvent is water.
[0076] In a preferred embodiment, a cleaning agent is used for cleaning. Using a cleaning agent for washing is beneficial to removing insoluble nanoparticles formed by the reduction of salt during the second reduction reaction, facilitating the subsequent first drying to form a pore structure, thereby facilitating obtaining a negative electrode composite material.
[0077] In order to further improve the removal rate of insoluble nanoparticles and facilitate the subsequent first drying to obtain the negative electrode composite material, preferably, the cleaning agent includes but is not limited to ethanol and / or water.
[0078] In order to improve the removal rate of the residual solvent in the negative electrode composite material and improve the purity of the negative electrode composite material, in a preferred embodiment, the first drying temperature is 60 to 80° C. and the time is 6 to 24 hours.
[0079] In a preferred embodiment, the second reduction reaction is carried out under a disturbance condition, and the disturbance includes but is not limited to at least one of stirring, shaking and ultrasound. Compared with other methods, the disturbance in the above manner is conducive to making the contact between the reaction raw materials more complete, which is conducive to improving the reaction efficiency of the second reduction reaction, thereby improving the coating effect of the graphene coating layer, and thus better playing the role of inhibiting the volume expansion of the negative electrode composite material.
[0080] In order to further improve the efficiency of the second reduction reaction, preferably, the stirring speed is 100-200 rpm, the oscillation frequency is 10-30 Hz, and the ultrasound frequency is 30-50 Hz.
[0081] In a preferred embodiment, the method for preparing the graphene oxide dispersion comprises: mixing graphene oxide with water to obtain the graphene oxide dispersion. The above preparation method is advantageous for pre-dispersing the graphene oxide in water, thereby facilitating improving the reaction efficiency of the second reduction reaction, and improving the coating effect of the graphene coating layer, thereby facilitating it to better play the role of inhibiting the volume expansion of the negative electrode composite material.
[0082] In order to increase the reaction efficiency of the second reduction reaction and improve the coating effect of the graphene coating layer, preferably, the mass concentration of graphene oxide is 6 to 10 mg / mL.
[0083] In order to further improve the dispersion effect of graphene oxide in water, preferably, ultrasonic treatment is performed during the mixing of graphene oxide and water.
[0084] In a preferred embodiment, the weight ratio of graphene oxide, salt and the second reducing agent is 1:(0.256-0.9):(1-9). The weight ratio of graphene oxide, salt and the second reducing agent includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the reaction efficiency of the second reduction reaction and improving the coating effect of the graphene coating layer, thereby helping it to better play the role of inhibiting the volume expansion of the negative electrode composite material.
[0085] In a preferred embodiment, step S1 includes: mixing a precursor solution with a dispersant and causing a first reduction reaction under the action of a first reducing agent, and successively performing centrifugal treatment and a second drying to obtain a core. After the first reduction reaction is completed, sequentially performing centrifugal treatment and a second drying is beneficial to removing the residual solvent in the core, which is beneficial to improving the purity of the core, thereby facilitating improving the ability of the lithiophilic silver sites in the core to induce uniform deposition and nucleation of lithium.
[0086] In order to further improve the separation efficiency of the core and the residual solvent and further improve the removal rate of the solvent, preferably, the rotation speed of the centrifugal treatment is 8000-15000 rpm and the time is 10-30 min.
[0087] In order to further improve the removal rate of the solvent and further improve the purity of the obtained kernel, preferably, the second drying temperature is 60-80° C. and the time is 6-12 hours.
[0088] The third aspect of the present application also provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein the negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer, and a metal lithium layer stacked in sequence, and the metal lithium layer is arranged between the negative electrode active material layer and the separator, wherein the negative electrode active material layer includes the above-mentioned negative electrode composite material provided by the present application. The silver element in the core of the above-mentioned negative electrode composite material provided by the present application can inhibit the growth of lithium dendrites and alleviate the "tip effect", and the copper element in the core can facilitate subsequent deposition to form an amorphous carbon coating layer with a more stable structure. The amorphous carbon coating and the graphene coating form a three-dimensional confined skeleton structure, which can provide more space to accommodate lithium, inhibit the expansion of the negative electrode composite material and the negative electrode sheet, thereby increasing the stability of the negative electrode sheet and improving the cycle performance of the lithium-ion battery; the amorphous carbon coating and the graphene coating are slip-connected, which facilitates the conduction of electrons from the graphene coating to the lithium-philic silver sites, constructing an internally and externally interconnected electronic network, effectively shortening the electron transmission path, and improving the electron transmission efficiency, thereby improving the energy density of the lithium-ion battery.
[0089] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0090] Example 1
[0091] A method for preparing a negative electrode composite material comprises the following steps:
[0092] (1) 152.9 mg of silver nitrate and 24.6 mg of copper nitrate were weighed and dissolved in 10 mL of deionized water to obtain a precursor solution. The precursor solution, 1.42 g of polyvinyl pyrrolidone (PVP, weight average molecular weight of 54,000) and 8.87 g of ethylene glycol were mixed and subjected to a first reduction reaction. After the reaction was completed, the core (equivalent to Ag) with an average particle size of 600 nm was obtained by centrifugation and drying. 90 Cu 10 ); wherein the temperature of the first reduction reaction is 180°C, the time is 30 min, the speed of the centrifugal treatment is 10000 rpm, the time is 15 min, and the drying temperature is 60°C, the time is 10 h;
[0093] The scanning electron microscope image of the prepared core is shown in Figure 1 As shown by Figure 1 It can be seen that it is irregularly shaped particles;
[0094] (2) A crucible containing 50 mg of the core was placed in a tube furnace (Hefei Kejing, OTF-1200X) for deposition with methane. Under the condition of an argon flow rate of 30 mL / min, the temperature was raised to 900°C at a heating rate of 5°C / min, and the argon flow rate was kept constant at 30 mL / min. Methane was introduced into the tube furnace at a rate of 35 mL / min. After 60 minutes, the introduction of methane was stopped. Under the condition of an argon flow rate of 30 mL / min, the temperature was lowered to 400°C at a cooling rate of 5°C / min and then allowed to cool naturally to obtain a core with an amorphous carbon coating layer on the surface;
[0095] (3) 60 mg of graphene oxide (McLean, S875745) was mixed with 10 mL of deionized water, and ultrasonically treated for 2 h to obtain a graphene oxide dispersion with a mass concentration of 6 mg / mL; 50 mg of the core with a surface-coated amorphous carbon coating layer obtained in step (2) was mixed with 10 mL of the graphene oxide dispersion to obtain a mixed solution, and ammonia water was added to adjust the pH to 9, and then 120 mg of hydrazine hydrate was added to carry out a second reduction reaction, firstly ultrasonically treated for 1 h, and then magnetically stirred at 70°C and 200 rpm for 23 h. After the reaction was completed, it was washed with deionized water three times and dried at 60°C for 10 h to obtain a negative electrode composite material.
[0096] The scanning electron microscope image of the negative electrode composite material prepared in Example 1 is as follows: Figure 2 The thickness of the amorphous carbon coating layer of the negative electrode composite material is 10 nm, and the thickness of the graphene coating layer is 500 nm.
[0097] Example 2
[0098] The difference from Example 1 is that in step (1), 265 mg of silver sulfate and 23.9 mg of copper sulfate are weighed and dissolved in 10 mL of deionized water to obtain a precursor solution, wherein the molar ratio of the Ag element to the Cu element in the precursor solution is 85:15, and the remaining steps are the same as in Example 1.
[0099] Ag of the negative electrode composite material prepared in Example 2 85 Cu 15 The average particle size of the core is 600 nm.
[0100] Example 3
[0101] The difference from Example 1 is that in step (1), 66.8 mg of silver acetate and 108.9 mg of copper acetate are weighed and dissolved in 10 mL of deionized water to obtain a precursor solution, wherein the molar ratio of the Ag element to the Cu element in the precursor solution is 40:60, and the remaining steps are the same as in Example 1.
[0102] Ag of the negative electrode composite material prepared in Example 3 40 Cu 60 The average particle size of the core is 800 nm.
[0103] Example 4
[0104] The difference from Example 1 is that in step (1), the molar ratio of Ag element to Cu element in the precursor solution is 15:85, and the remaining steps are the same as Example 1.
[0105] Ag of the negative electrode composite material prepared in Example 4 15 Cu 85 The average particle size of the core is 800 nm.
[0106] Example 5
[0107] The difference from Example 1 is that in step (1), the molar ratio of Ag element to Cu element in the precursor solution is 10:90, and the remaining steps are the same as Example 1.
[0108] Ag of the negative electrode composite material prepared in Example 5 10 Cu 90 The average particle size of the core is 2000 nm.
[0109] Example 6
[0110] The difference from Example 1 is that in step (1), the molar ratio of Ag element to Cu element in the precursor solution is 99:1, and the remaining steps are the same as Example 1.
[0111] Ag of the negative electrode composite material prepared in Example 6 99 Cu 1 The average particle size of the core is 300 nm.
[0112] Example 7
[0113] The difference from Example 1 is that: in step (1), the precursor solution, 1.73g polyvinylpyrrolidone (PVP, molecular weight 50000) and 1.2g ascorbic acid are mixed and a first reduction reaction is carried out at 170°C; wherein the molar ratio of the dispersant to the silver salt is 1:1, and the molar ratio of the first reducing agent to the silver salt is 1:1; in step (3), an equal amount of ascorbic acid is used to replace hydrazine hydrate, and a second reduction reaction is carried out at 60°C, and the remaining steps are the same as in Example 1.
[0114] The average particle size of the core of the negative electrode composite material prepared in Example 7 is 500 nm, and the thickness of the graphene coating layer is 500 nm.
[0115] Example 8
[0116] The difference from Example 1 is that: in step (1), the precursor solution, 1.7g polyvinyl pyrrolidone (PVP, weight average molecular weight of 40000) and 85mg ethylene glycol are mixed and a first reduction reaction is carried out at 200°C; wherein the molar ratio of the dispersant to the silver salt is 10:1, and the molar ratio of the first reducing agent to the silver salt is 0.2:1; in step (3), the mass concentration of the graphene oxide dispersion is 8mg / mL, the amount of the second reducing agent hydrazine hydrate added is 100mg, and a second reduction reaction is carried out at 90°C; wherein the weight ratio of graphene oxide to the second reducing agent is 1:0.8; and the remaining steps are the same as in Example 1.
[0117] The average particle size of the inner core of the negative electrode composite material prepared in Example 8 is 50 nm, and the thickness of the graphene coating layer is 50 nm.
[0118] Example 9
[0119] The difference from Example 1 is that in step (2), the deposition time is 360 min, and the remaining steps are the same as Example 1.
[0120] The thickness of the amorphous carbon coating layer of the negative electrode composite material prepared in Example 9 is 20 nm.
[0121] Example 10
[0122] The difference from Example 1 is that in step (2), the deposition time is 20 minutes, and the remaining steps are the same as Example 1.
[0123] The thickness of the amorphous carbon coating layer of the negative electrode composite material prepared in Example 10 is 3 nm.
[0124] Embodiment 11
[0125] The difference from Example 1 is that in step (3), the mass fraction of the graphene oxide dispersion is 2 mg / mL, and the remaining steps are the same as in Example 1.
[0126] The thickness of the graphene coating layer of the negative electrode composite material prepared in Example 11 is 50 nm.
[0127] Example 12
[0128] The difference from Example 1 is that the temperature of the first reduction reaction in step (1) is 220° C. and the time is 10 min. The remaining steps are the same as Example 1.
[0129] Embodiment 13
[0130] The difference from Example 1 is that the temperature of the second reduction reaction in step (3) is 120° C. and the time is 4 h. The remaining steps are the same as Example 1.
[0131] Embodiment 14
[0132] The difference from Example 1 is that in step (3), 50 mg of the core coated with an amorphous carbon coating layer, 10 mL of a graphene oxide dispersion with a mass concentration of 6 mg / mL and 3 mL of KMnO with a mass concentration of 10 mg / mL are mixed. 4 The aqueous solutions were mixed to obtain a mixed solution, and ammonia water was added to adjust the pH of the mixed solution to 9, and 120 mg of hydrazine hydrate was added to the mixed solution for a second reduction reaction. After the reaction was completed, the mixed solution was washed with deionized water for 3 times and dried at 60° C. for 10 h to obtain a negative electrode composite material.
[0133] The graphene coating layer of the negative electrode composite material prepared in Example 14 has a thickness of 500 nm, a porosity of 32.93%, and a specific surface area of 117.23 cm 2 / g.
[0134] Comparative Example 1
[0135] The difference from Example 1 is that the preparation method of the precursor solution in step (1) is: 100 mg of copper acetate is dissolved in 100 mL of deionized water to obtain a precursor solution, and the remaining steps are the same as Example 1.
[0136] The core of the negative electrode composite material prepared in Comparative Example 1 is only Cu, and does not contain silver element.
[0137] Comparative Example 2
[0138] The difference from Example 1 is that step (2) is omitted, the core obtained in step (1) is directly mixed with the graphene oxide dispersion and hydrazine hydrate to carry out the second reduction reaction, and the remaining steps are the same as those in Example 1.
[0139] The negative electrode composite material prepared in Comparative Example 2 is a core whose surface is only covered with a graphene coating layer.
[0140] Comparative Example 3
[0141] The difference from Example 1 is that step (3) is omitted, the core with a surface-coated amorphous carbon coating layer obtained in step (2) is used as the negative electrode composite material, and the remaining steps are the same as in Example 1.
[0142] The negative electrode composite material prepared in Comparative Example 3 is a core with an amorphous carbon coating layer on the surface.
[0143] A method for preparing a lithium ion battery comprises the following steps:
[0144] (1) Preparation of negative electrode sheet: The negative electrode composite materials prepared in the above-mentioned Examples 1 to 14 and Comparative Examples 1 to 3 were respectively used as negative electrode active materials, and the negative electrode active materials, binder PAA (polyacrylic acid) and dispersant CMC (carboxymethyl cellulose) were mixed in a weight ratio of 85:10:5, and the slurry was coated on a copper foil with a thickness of 8 μm, and then placed in an oven at 80°C for 12 hours. The sheet was cut into a disc with a diameter of 14 mm and placed in a dry argon atmosphere glove box for storage; 5 mAh / cm 2 of lithium to obtain a negative electrode;
[0145] (2) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate (LFP), the conductive agent (Super P conductive carbon), and the binder polyvinylidene fluoride are mixed in a weight ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added. The mixture is stirred in a vacuum mixer until the system is uniform to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is about 72wt%; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the mixture is dried, and then cold pressed, cut into pieces, and slit, and then dried in a vacuum condition of about 85°C for about 4h to obtain a positive electrode;
[0146] (3) Preparation of separator: Polyethylene (PE) with a thickness of about 20 μm was used as the separator;
[0147] (4) Preparation of electrolyte: In a dry argon atmosphere glove box, 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO) were added. 3 ); wherein the mass percentage of lithium nitrate is 2%, the concentration of lithium bis(trifluoromethanesulfonyl)imide is 1 mol / L, and the mixed solution is placed on a magnetic stirrer and stirred for 12 hours to ensure that the solid is fully dissolved to prepare an electrolyte;
[0148] (5) Preparation of deposited lithium metal negative electrode sheet: stack the negative electrode sheet, separator, and lithium metal negative electrode in order, wherein the negative electrode current collector is located on the side of the negative electrode sheet away from the separator; after welding the electrode ear, place it in an outer packaging aluminum plastic film, vacuum package, stand, and discharge at a constant current (0.05 mAh / cm 2 g constant current discharge, with a cut-off voltage of -1V) to obtain a soft-pack laminated lithium metal battery. The soft-pack battery is then disassembled in a dry argon atmosphere glove box to obtain a negative electrode sheet with deposited metal lithium;
[0149] (6) Preparation of lithium-ion battery: The negative electrode shell, negative electrode plate, polyethylene separator with a thickness of 15 μm, and positive electrode plate are stacked in order, wherein the negative electrode current collector is located on the side of the negative electrode plate away from the polyethylene separator, and the metal lithium layer is located on the side of the negative electrode plate close to the polyethylene separator. 75 μL of electrolyte is injected, and finally the spring sheet and positive electrode shell are stacked in order to assemble a button-type lithium-ion battery.
[0150] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples of the present application were subjected to the following performance tests, including:
[0151] (1) The test conditions for the battery discharge capacity in grams are as follows: Place the lithium metal battery in a 25°C constant temperature box and let it stand for 30 minutes to allow the battery to reach a constant temperature; Charge the constant temperature lithium metal battery at a constant current of 0.1C to 3.7V, and then discharge it at a constant current of 0.1C to 2.5V; this is one charge and discharge cycle, with the first discharge capacity as 100%, and read and record the first cycle discharge capacity in grams;
[0152] (2) Charge transfer resistance R CT The test conditions are as follows: place the lithium metal battery in a 25°C constant temperature box and let it stand for 30 minutes to allow the battery to reach a constant temperature; connect the battery to an impedance tester with a frequency range of 0.01 to 10000 Hz and an amplitude of 10 to 20 mV to test the impedance of the lithium metal battery, read and record the impedance value, and use the impedance complex plane diagram to analyze the data to obtain the impedance of the lithium metal battery;
[0153] (3) The test conditions for cycle performance are as follows: the lithium-ion battery is placed in a 25°C thermostat and allowed to stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature; the lithium-ion battery that has reached a constant temperature is placed on a charge and discharge device, and activated three times at 0.02C, and then a cycle performance test is performed, using 0.5C charging to 3.7V and 1C discharge to 2.5V, and the cycle is repeated with the first discharge capacity as 100%, and the test is stopped when the discharge capacity decays to 75%, and the number of cycles is recorded;
[0154] (4) The test conditions for rate performance are as follows: charge and discharge cycles are performed at a constant current rate of 2C at 25°C and a voltage range of 2.5 to 3.7V.
[0155] The test results are shown in Table 1 below.
[0156] Table 1
[0157]
[0158] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects.
[0159] By comparing Example 1 and Comparative Example 1, it can be seen that the core in the present application includes silver and copper elements. Silver is used as a lithium-philic site, which can induce uniform lithium deposition and nucleation during the cycle of the lithium-ion battery. Silver has a good ability to alloy and de-alloy with lithium, and ensures the long-term effectiveness of the lithium-philic sites in the negative electrode active material layer in the negative electrode sheet during repeated lithium deposition and stripping, thereby inhibiting the growth of lithium dendrites and alleviating the "tip effect", thereby improving the structural stability of the negative electrode composite material, and further improving the cycle performance and rate performance of the lithium-ion battery.
[0160] By comparing Example 1, Comparative Examples 2 and 3, it can be seen that the present application uses a carbon coating layer and a graphene coating layer to form a three-dimensional confined skeleton structure, thereby providing more space to accommodate lithium and inhibiting the expansion of the negative electrode composite material and the negative electrode plate; under the dual action of the carbon coating layer and the graphene coating layer, the lithium-philic silver sites in the inner core can be confined and fixed in a uniformly distributed position, and the dual confined skeleton structure formed by the two not only provides space for the volume expansion of the negative electrode composite material, but also confines the changes brought about by the volume expansion inside the structure, thereby increasing the stability of the negative electrode plate, thereby improving the cycle performance and rate performance of the lithium ion battery; the amorphous carbon coating layer and the graphene coating layer themselves have excellent conductivity, and the amorphous carbon coating layer and the graphene coating layer are slip-connected, so that electrons are easily conducted from the graphene coating layer to the lithium-philic silver sites, and an internal and external interconnected electronic network is constructed, which effectively shortens the electron transmission path, is conducive to reducing the charge transfer resistance, and improving the electron transmission efficiency, thereby improving the energy density of the lithium ion battery.
[0161] By comparing Examples 1 to 6, it can be seen that the molar ratio of the silver element in the silver salt to the copper element in the copper salt includes but is not limited to the above range. Limiting it within the above range is beneficial to provide enough lithium-philic silver sites for the negative electrode composite material, which is beneficial to make the lithium deposition more uniform during the cycle of the lithium-ion battery, thereby facilitating the inhibition of the growth of lithium dendrites and alleviating the "tip effect", thereby facilitating the improvement of the structural stability of the negative electrode composite material and the improvement of the cycle performance and rate performance of the prepared lithium-ion battery; on the other hand, during the deposition process, the catalytic effect of the copper element in the core can be better exerted, thereby improving the deposition effect of the amorphous carbon coating layer, and obtaining a core with an amorphous carbon coating layer coated on the surface, which is beneficial to improving the energy density of the lithium-ion battery.
[0162] By comparing Examples 1, 7 and 8, it can be seen that the molar ratio of the silver salt, the copper salt and the dispersant includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the reaction efficiency of the first reduction reaction, and is beneficial to inhibiting the agglomeration of the core particles obtained by the first reduction reaction, thereby helping to improve the distribution uniformity of the silver-copper alloy; the molar ratio of the silver salt, the copper salt and the first reducing agent includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the reaction efficiency of the first reduction reaction, helping to improve the yield of the core, helping to make the particle size of the obtained core within a more suitable range, helping to improve the density of the core, thereby helping to improve the electrochemical performance of the lithium-ion battery.
[0163] By comparing Examples 1, 9 and 10, it can be seen that the time for amorphous carbon deposition includes but is not limited to the above range. Limiting it within the above range is beneficial to making the weight ratio of the core to the carbon source within a more suitable range, thereby helping to improve the specific surface area, conductivity and structural stability of the negative electrode composite material, providing more space for the volume expansion of the negative electrode composite material, and improving the structural stability of the negative electrode composite material, thereby helping to improve the cycle performance and energy density of the lithium-ion battery.
[0164] By comparing Examples 1 and 11, it can be seen that the mass concentration of the graphene oxide dispersion includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the reaction efficiency of the second reduction reaction and improving the coating effect of the graphene coating layer, thereby better playing the role of inhibiting the volume expansion of the negative electrode composite material, and further helping to improve the electrochemical performance of the lithium-ion battery.
[0165] By comparing Examples 1, 12 and 13, it can be seen that the temperature and time of the first reduction reaction include but are not limited to the above ranges, and limiting them within the above ranges is beneficial to improving the reaction efficiency of the first reduction reaction and improving the yield of the inner core; the temperature and time of the second reduction reaction include but are not limited to the above ranges, and limiting them within the above ranges is beneficial to improving the reaction efficiency of the second reduction reaction and improving the coating effect of the graphene coating layer, thereby better playing the role of inhibiting the volume expansion of the negative electrode composite material, and further helping to improve the electrochemical performance of the lithium-ion battery.
[0166] By comparing Examples 1 and 14, it can be seen that introducing salt in the second reduction reaction is beneficial to reducing the salt into insoluble nanoparticles during the second reduction reaction, which is beneficial to its attachment to the graphene oxide sheet, promoting the overlapping of the graphene sheet, and improving the close bonding between the graphene sheet and the amorphous carbon coating. After washing and removing the insoluble nanoparticles, pores can be formed at the positions of the original insoluble nanoparticles on the graphene sheet, which is beneficial to improving the transmission efficiency of electrons, and further beneficial to improving the electrochemical performance of the lithium-ion battery.
[0167] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0168] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A negative electrode composite material, characterized in that: From inside to outside, the negative electrode composite material includes a core, an amorphous carbon coating layer and a graphene coating layer in sequence, wherein the core includes silver elements and copper elements.
2. The negative electrode composite material according to claim 1, characterized in that: The core is a silver-copper alloy having the general formula Ag x Cu 100-x , wherein x is any value between 15 and 90; preferably, x is any value between 40 and 90.
3. The negative electrode composite material according to claim 1 or 2, characterized in that: The average particle size of the core is 500 to 3000 nm; Preferably, the thickness of the amorphous carbon coating layer is 5 to 20 nm; Preferably, the thickness of the graphene coating layer is 100 to 500 nm; Preferably, the graphene coating layer comprises a graphene porous material; Preferably, the graphene coating has a porosity of 20-50% and a specific surface area of 50-250 cm 2 / g.
4. A method for preparing the negative electrode composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, mixing a precursor solution containing silver and copper elements with a dispersant and causing a first reduction reaction to occur under the action of a first reducing agent to obtain a core; Step S2, under inert atmosphere conditions, depositing an amorphous carbon coating layer on the surface of the core to obtain a core with the surface coated with the amorphous carbon coating layer; wherein a carbon source is introduced during the deposition process; Step S3, mixing the core with the amorphous carbon coating layer on the surface with a graphene oxide dispersion and causing a second reduction reaction under the action of a second reducing agent, and obtaining the negative electrode composite material after a first drying.
5. The method for preparing the negative electrode composite material according to claim 4, characterized in that: The method for preparing the precursor solution comprises: mixing a silver salt, a copper salt and water to obtain the precursor solution; Preferably, the molar ratio of the silver element in the silver salt to the copper element in the copper salt is x:(100-x), wherein x is any value in the range of 15 to 90, and more preferably x is any value in the range of 40 to 90; Preferably, the molar ratio of the silver salt, the copper salt and the dispersant is (1-8):1:1; Preferably, the molar ratio of the silver salt, the copper salt and the first reducing agent is (1-5):1:2; Preferably, the silver salt is selected from one or more of the group consisting of silver nitrate, silver sulfate and silver acetate; Preferably, the copper salt is selected from one or more of the group consisting of copper nitrate, copper sulfate, copper acetate, copper chloride and basic copper sulfate; Preferably, the dispersant is selected from one or more of the group consisting of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, carboxymethyl cellulose, polyacrylamide, guar gum and fatty acid polyethylene glycol esters; more preferably, the weight average molecular weight of the polyvinyl pyrrolidone is 4000 to 130000; Preferably, the temperature of the first reduction reaction is 170-200° C., and the time is 20-40 min.
6. The method for preparing the negative electrode composite material according to claim 4 or 5, characterized in that: The deposition is performed by chemical vapor deposition, preferably at a temperature of 900 to 1000° C. and a time of 60 to 360 min; Preferably, the weight of the inner core to the volume ratio of the carbon source is (20-100) mg: (2100-12600) mL; Preferably, the carbon source is selected from one or more C1-C4 hydrocarbon compounds; more preferably, one or more C1-C4 alkanes; Preferably, the inert atmosphere is selected from argon, or a mixture of hydrogen and nitrogen, or a mixture of hydrogen, nitrogen and argon.
7. The method for preparing the negative electrode composite material according to any one of claims 4 to 6, characterized in that: The step S3 comprises: mixing the core with the amorphous carbon coating layer on the surface, the graphene oxide dispersion, salt and solvent, and performing the second reduction reaction under the action of the second reducing agent, and then washing and performing the first drying in sequence to obtain the negative electrode composite material; Preferably, the temperature of the second reduction reaction is 60-90°C and the time is 6-24h; Preferably, the first reducing agent and the second reducing agent are each independently selected from one or more of the group consisting of ethylene glycol, hydrazine hydrate, vinylene carbonate, thiourea, hydroiodic acid, urea, ascorbic acid, n-butanol, sodium bisulfite and sodium citrate; Preferably, the salt is selected from one or more of the group consisting of KMnO4, Na2S2O3, FeCl3 and Fe2(SO4)3; Preferably, the solvent is water; Preferably, the washing is performed using a cleaning agent, preferably the cleaning agent is selected from ethanol and / or water; Preferably, the first drying is carried out at a temperature of 60 to 80° C. and for a time of 6 to 24 hours.
8. The method for preparing the negative electrode composite material according to claim 7, characterized in that: The second reduction reaction is carried out under a disturbance condition, wherein the disturbance is selected from at least one of stirring, shaking and ultrasound; Preferably, the stirring speed is 100-200 rpm, the oscillation frequency is 10-30 Hz, and the ultrasound frequency is 30-50 Hz; Preferably, the method for preparing the graphene oxide dispersion comprises: mixing graphene oxide with water to obtain the graphene oxide dispersion; preferably, the mass concentration of the graphene oxide is 6 to 10 mg / mL; preferably, ultrasonic treatment is performed during the mixing of graphene oxide and water; Preferably, the weight ratio of the graphene oxide, the salt and the second reducing agent is 1:(0.256-0.9): (1~9)。 9. The method for preparing the negative electrode composite material according to claim 4, characterized in that: The step S1 comprises: mixing the precursor solution with the dispersant and causing the first reduction reaction to occur under the action of the first reducing agent, and then subjecting the mixture to centrifugal treatment and second drying to obtain the core; Preferably, the rotation speed of the centrifugal treatment is 8000-15000 rpm, and the time is 10-30 min; Preferably, the second drying is carried out at a temperature of 60 to 80° C. and for a time of 6 to 12 hours.
10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The negative electrode plate comprises a negative electrode current collector, a negative electrode active material layer and a metal lithium layer which are stacked in sequence, and the metal lithium layer is arranged between the negative electrode active material layer and the separator, wherein the negative electrode active material layer comprises the negative electrode composite material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Silver-carbon composite metal lithium negative electrode and preparation method thereof
CN115172670A